Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1108/14637150410567875
|View full text |Cite
|
Sign up to set email alerts
|

Business process development in project‐based industry

Abstract: The strategic focus of organisations today is on the customer and internal and external processes. This paper presents a systematic approach to project process development and identifies key aspects of long-term process evaluation. A framework for process development is presented with special emphasis on value-adding activities in engineering, procurement, and construction (EPC) projects. The framework provides a better understanding of the dynamic processes and critical interfaces in inter-organisational netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 9 publications
0
33
0
4
Order By: Relevance
“…(3) Horizontal: intra-functional or cross-functional. Sandhu and Gunasekaran (2004) are the only authors found that define a process as a series of activities that "involves an independent functional unit". A dominating view seems to be that processes are horizontal and cross-functional (see for instance Jacobson, 1995;Armistead and Machin, 1997;Lee and Dale, 1998;Llewellyn and Armistead, 2000).…”
Section: Process Definitions Categorizations and Rolesmentioning
confidence: 99%
“…(3) Horizontal: intra-functional or cross-functional. Sandhu and Gunasekaran (2004) are the only authors found that define a process as a series of activities that "involves an independent functional unit". A dominating view seems to be that processes are horizontal and cross-functional (see for instance Jacobson, 1995;Armistead and Machin, 1997;Lee and Dale, 1998;Llewellyn and Armistead, 2000).…”
Section: Process Definitions Categorizations and Rolesmentioning
confidence: 99%
“…Añadir valor al cliente / Enfoque al cliente (Hung, 2006); (Bullita, 2006) en (Kohlbacher, 2010); (Classe & Mundle, 1997) en (Kohlbacher, 2010); (Küng & Hagen, 2007); (Furey, 1993); (Silvestro & Westley, 2002); (Clemmer, 1994); (Paper & Chang, 2005); (Lee & Dale, 1998); (Hill & Collins, 1998); (Corallo et al, 2010); (Melan, 1989); (Armistead & Pritchard, 1999); (Biazzo & Bernardi, 2003); (Sandhu & Gunasekaran, 2004) Aumento de la competencia nacional y/o internacional (Hung, 2006); (Classe & Mundle, 1997) en (Kohlbacher, 2010); (Küng & Hagen, 2007); (Feltes & Karuppan, 1995); (Armistead & Machin, 1998); (Clemmer, 1994); (Hill & Collins, 1998); (Ongaro, 2004) Necesidad de ahorrar dinero mediante la reducción de costes o el aumento de la productividad (Paper & Chang, 2005); (Clemmer, 1994); (Davenport & Short, 1990); (Palmberg, 2010); (Hill & Collins, 1998); (Corallo et al, 2010) Como parte de un proyecto más amplio (sistema de calidad total, ISO 9000; adopción modelo de calidad, etc.) (Paper & Chang, 2005); (Pauls, 2006) en (Kohlbacher, 2010); (Armistead & Machin, 1998); …”
Section: Razones O Motivos Autoresunclassified
“…(Paper & Chang, 2005); (Pauls, 2006) en (Kohlbacher, 2010); (Armistead & Machin, 1998); (Corallo et al, 2010) La empresa no era capaz de hacer frente al crecimiento (Pauls, 2006) en (Kohlbacher, 2010) Tasa de fracaso de los productos muy elevada/ mejorar la calidad (Wahlich, 2004) en (Kohlbacher, 2010); (Davenport & Short, 1990) Necesidad de mejorar los productos existentes, crear nuevos o entrar en nuevas líneas de negocio para continuar siendo competitivos (Paper & Chang, 2005); (Melan, 1989); (Sandhu & Gunasekaran, 2004); (McAdam & McCormack, 2001) Mejorar la efectividad organizacional (Jones, 1994) en (Palmberg, 2010); (Elzinga et al, 1995); (Armistead & Pritchard, 1999) Eliminar las barreras existentes entre los departamentos funcionales (Paper & Chang, 2005); (Jones, 1994) en (Palmberg, 2010); (Llewellyn & Armistead, 2000) Necesidad de mejorar la gestión de los recursos de IT (Paper & Chang, 2005); (Sandhu & Gunasekaran, 2004); (Hill & Collins, 1998); (Ongaro, 2004) Motivación interna de la propia empresa (Mittermaier & Braun, 2004) en (Kohlbacher, 2010); (Clemmer, 1994) Una crisis obligó a analizar las prácticas que se estaban llevando a cabo (GropengieBer, 1997) en (Kohlbacher, 2010) Conseguir reducciones de tiempo (Davenport & Short, 1990); (Ongaro, 2004) Para identificar oportunidades para subcontratar (Lindsay, Downs & Lunn 2003…”
Section: Razones O Motivos Autoresunclassified
“…For example, Porter and Millar [19] group business process into value-adding primary process and infrastructural support process and Davenport and Short [20] provide similar typology of operationally-orientated and management-orientated business process. Although Manganelli and Klein [15] and Sandhu and Gunasekaran [21] have further divide support/management-orientated business process into hand-off and control process or strategic process and administrative process, their rationale to distinct supporting management business process from primary operation business process remains the same.…”
Section: Business Process In Constructionmentioning
confidence: 99%